Homeownership and housing consumption change in Urban China: Guangzhou under market transition. Issue 5 (28th May 2017) - Li, Si-ming
ABSTRACT: Homeownership attainment is often seen as the first step in climbing the housing ladder and the building of wealth through acquisition of housing equity. While a number of authors have examined the issue of homeownership switch in China under market transition, the present paper is probably the first study on the extent of housing improvement in conjunction with and after the attainment of homeownership. Based on a household survey conducted in 2010, the study shows that ownership attainment in Guangzhou is generally accompanied by marked housing improvements, and subsequent moves bring further but percentage-wise much smaller improvements. While institution-related factors such as nature of work unit and occupational status might continue to be important, their effects on housing improvements are likely to be felt mainly through the income variable. But hukou status remains significant. More specifically, former peasants on the urban–rural fringe with claim to landownership rights have benefited most from the market-oriented land and housing reform.